Review of Trial Therapies and Treatment for COVID-19: Lessons for Indonesia - Mukhlida, Halma Zahro; Maulida, Hilma Hasro; Khairunnisa, Gunanti; Mantrono, Margaretha Josephine; Hartono, Risky Kusuma; Rindu, Rindu; Purnamasari, Eka R W; Meirawan, Rizky Fajar (Kesmas, 2020)
The infectious disease from Coronavirus Disease 2019, or COVID-19, has quickly spread world-wide since 2019. Therapies for managing COVID-19 have yet to be confirmed as medication for the severe sickness that the disease may cause. This study aimed to review the previous research of the efficacy of trial therapy and treatment to the patients in the hospital with COVID-19. Using PRISMA guidelines as a method for conducting a systematic literature review, a total of 67 articles were collected from several online journal databases. Various therapies were found that are effective in the treatment and management of COVID-19. In accordance with the inclusion and exclusion criteria of this study, a total of 8 articles were selected. The study showed that several therapies are effective in managing the severe illness, can be used as COVID-19 treatment. Combination of medicine have shown the effectiveness of clinical improvements and recovery rate in a short time compared to single medicine. Nevertheless, further study into effective therapies for COVID-19 must be continued to find the best therapy and treatment.